DIGITAL TECHNOLOGIES AND THEIR IMPACT ON SOCIETAL DEVELOPMENT - Jamаlova Gulnora Gulomovna (Bright Mind Publishing, 2025)
Throughout human history, technical innovation has been a primary driver of significant social, economic, political, and cultural transformations. These transformations have become even more visible in the internet era. This article deals with the issues based on analyzing the impact of digital technologies—particularly computers and the Internet—on society. It also investigates the role of digital instruments in globalization, which has a huge impact on societies around the world. The study demonstrates the revolutionary potential of digital advances in transforming communication, business, governance, and daily life around the world.
Keywords: Technology, digital innovation, human society, economy, information, globalization, automation.